Efficacy and Safety of Pilocarpine Eye Drops Combinations for Treating Presbyopia in a Thai Population: A Randomized Crossover Trial - Surachatkumtonekul, Thammanoon; Jutasompakorn, Pinpilai; Klinniyom, Anchalika; Sermsripong, Wasawat; Hokierti, Kiatthida; Sangsre, Prapasson; Rungsiri, Ketchanya (Siriraj Medical Journal, 2024)
Objective: This study aimed to assess and compare the effectiveness and side effects of various concentrations of pilocarpine eye drops (1.5%, 1.25%, and 1%), with and without 0.1% brimonidine, in treating presbyopia, specifically in a Thai population. Materials and Methods: A prospective, randomized, double-blinded, and crossover trial was conducted at Siriraj Hospital from August 2022 to April 2023. The study included emmetropic individuals aged 40 to 60 with presbyopia (near visual acuity not exceeding J1+) and refractive errors within +/- 0.5D. The ten subjects were assigned randomly to 6 groups for the different concentrations and type of eyedrops using a computer-generated systematic randomization to receive 1.5%, 1.25%, and 1% pilocarpine with and without 0.1% brimonidine. And visual outcomes including visual acuity at distance and near were measured at 2, 4, and 6 hours post-application, with adverse effects monitored. Primary outcome was visual acuity at near after applied topical eye drops. Results: Among the 10 participants (30% male, median age 46.5 years old), 1.25% pilocarpine and combined 1.25% pilocarpine + 0.1% brimonidine significantly improved near visual acuity at all time points (statistically significant with Bonferroni correction). Adverse effects, such as dry eye and irritation, were more common with 1.5% pilocarpine + 0.1% brimonidine. Conclusion: In this preliminary study, 1.25% pilocarpine and 1.25% pilocarpine + 0.1% brimonidine showed promise in effectively treating presbyopia in the Thai study population, with acceptable side effect rates. Further research with larger sample sizes is needed to confirm these findings and provide more robust insights into presbyopia management in the Asian demographic.